PROFILE OF THE LIFESTYLE OF THE SWIMMERS OF THE CATEGORY " THE " OF THE GAMES OF THE YOUTH FROM PARANÁ, FINAL PHASE - 2005 (Fiep Bulletin - online, 2015)
It is known that the lifestyle depends of the behaviors and the individuals' attitudes, where these life habits can interfere in the most several situations for the which the individuals pass, among them, the sporting practice and the constant looks for better results. In the Games of the Youth from Paraná they announce athletes with a great technical level, and for this the athletes possess a routine of trainings desgastante, and it can interfere in the lifestyle of the same ones. Leaving of this premise, this research has as main objective to identify the profile of the swimmers' lifestyle of the category " THE " of the Games of the Youth from Paraná, Final Phase - 2005. This research is characterized as descriptive and it possesses as 57 swimmers' sampling, among them 25 belonging to the feminine sex and 32 belonging to the masculine sex, in the age group among 15 to 17 years, chosen aleatoriamente. The instrument used for the collection of data it was a questionnaire proposed by NAHAS (2003) call of " profile of individual " lifestyle that approaches the following components: nutrition, physical activity, preventive behavior, relationships and control of the stress. The completion of the questionnaire felt in the places and period of the competition in the city of Toledo-Pr. After the collection of the data it is possible to conclude that the swimmers present a good lifestyle, same tends some aspects that they can be gotten better, among them the component nutrition and the preventive behavior.
Keywords: Lifestyle - Swimmers - Games of the Youth